Invitation to holy company : being the memoirs of ten direct disciples of Sri Ramakrishna - Jnanatmananda, Swami (Sri Ramakrishna Math, 1979)
Reminiscences of the author's association with ten disciples of Ramakrishna, 1836-1886, Hindu saint.